Boofheads with deep voices: sexual dimorphism in the Magpie Goose Anseranas semipalmata - Whitehead, Peter J (Wildfowl, 1998)
Magpie geese use a unique polygynous mating system, involving apparently stable trios of one male and two females. Plumage shows little sexual differentiation, but there is considerable dimorphism in body size, with males being about 30% heavier. The males also develop an extraordinarily elongated and elaborately folded trachea early in life, whereas less than 85% of females show even minor tracheal elaboration. Head height, a measure of the size of a cranial bump of spongy bone increases with age in both sexes, but most markedly in males. Males found in association with nests have larger bumps and highly elaborated tracheal morphology. The deeper and louder calls associated with gross tracheal elongation, which probably comprises respiratory exchange, may influence female choice of mates by providing a reliable signal of male viability. Despite significant overlap in individual dimensions, especially among younger birds, more than 92% can be accurately sexed using a discriminant function based on three simple measures (head-bill length, head height, and tarsus length). Discrimination can be improved by checking birds assigned as females against an index of tracheal morphology. Simulations indicate that bias in estimates of sex ratios arising from application of the discriminant function, when combined with tracheal examination, is likely to be less than 2%.